The effect of fair trade affiliation on child schooling: Evidence from a sample of Chilean honey producers - Leonardo Becchetti; Stefano Castriota; Melania Michetti (Fondazione Eni Enrico Mattei (FEEM), 2012)
We evaluate the impact of fair trade (FT) affiliation on child schooling within a sample of Chilean honey producers with a retrospective panel data approach. From a theoretical point of view we argue that FT should have a positive effect on child schooling since it generates a short run pure income effect together with a medium run productivity effect on both adult and child wages. On the other hand, because of the higher productivity generated by the medium run effect, the opportunity cost of child education increases if they work with their parents. The direction of the impact of FT affiliation on child schooling is therefore uncertain and requires empirical testing. Our econometric findings document a positive and significant impact of affiliation years on child schooling after controlling for endogeneity and heterogeneity between the treatment and control sample.
Keywords: O19; O22; D64; J22; 330; Fair Trade; Child Schooling; Impact Study